Kebijakan Publik Dalam Mendorong Inklusi Sosial Dengan Penanggulangan Pencemaran Lingkungan - Salfina Nur Imayati; Hayat Hayat; Sunariyanto Sunariyanto (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2023)
Environmental damage as a from of change caused by human interaction, both these changes are direct and indirect. This change becomes a new problem that is difficult to overcome. The problem of environmental damage is not a problem of an individual, an organization, but rather it is a common problem that requires joint handling as well. This research aims to find out how the government’s policy to tackle environmental pollution and how public policy encourages social inclusion in tackling pollution. This research uses a juridical approach by examining government policies. This research managed to find out what are the public policies in dealing with environmental pollution. The existence of the government’s role in encouraging social inclusion in tackling environmental pollution as a from of government participation in environmental pollution